Eklezjalno-teologiczne podstawy praktyki pokutnej wprowadzonej przez Cypriana w Kartaginie - Słomka, Jan (Śląskie Studia Historyczno-Teologiczne, 2023)
The mid-third century persecutions of Christians spread over the entire Roman Empire. Thank to Cyprian’s correspondence, we are familiar with their course and the developments in the African church after their termination. After the persecutions ceased, Cyprian commenced the process of reconciliation in the Church, establishing the rules for the reinstatement of the lapsed. He argued against the practice of recommendation letters issued by the Confessors on the one hand, and against the rigorists who denied the fallen any possibility of returning to the Church on the other. The Confessors pointed to their unique relationship with the crucified Christ resulting from the tortures they had withstood. The rigorists claimed that only baptism cleansed heavy sins, including the denunciation of Christ, therefore, it is impossible for the Church to forgive those sins again after baptism. Cyprian adopted the following principle: ecclesiastical communion may be offered, but it has to be preceded by penance, and it is only the bishop or priests acting on his behalf that have the right to grant it. He justified the possibility of restoring the lapsed by claiming that the Church was a community of repenting sinners. Granting the ecclesiastical communion is without prejudice to the Lord’s decision at the Last Judgment, but it gives hope and support to the sinner, so that he may persevere in his penance. Cyprian’s objection against Confessors granting ecclesiastical communion – the practice that was well established in the Church and considered as lawful – resulted directly from his understanding of the Church as a community gathered around the bishop. As the successors of the Apostles, bishops are depositaries of the gifts and executors of the commands which Christ has left to His Church. Reinstating the lapsed, they act on behalf of the Church, without invoking their personal merits, as the Confessors did.